The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1111/pde.14049
|View full text |Cite
|
Sign up to set email alerts
|

The association between atopic dermatitis and serum 25‐hydroxyvitamin D in children: Influence of sun exposure, diet, and atopy features—A cross‐sectional study

Abstract: Background Previous studies have linked low serum vitamin D (VD) or 25‐hydroxyvitamin D (25(OH)D) levels with increased severity of atopic dermatitis (AD) in children. Objective To investigate the association between serum VD (25(OH)D) levels and AD and AD severity, considering the influence of diet and sun exposure. Methods We performed a prospective cross‐sectional study of healthy controls and children diagnosed with AD. Participants were recruited between January 2011 and December 2012, and the following p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 39 publications
0
7
0
4
Order By: Relevance
“…Most of the studies showed serum 25(OH)D was significantly lower in AD than HC. Of the 14 studies, only Sanmartin et al [13] and Di Filippo et al [25] showed higher 25(OH)D for AD compared with HC, but these differences were not significant. Three sub-analyses were conducted for latitude, geographical continent, and quality of study (Supplementary Figs.…”
Section: Serum Vitamin D In Atopic Dermatitis and Healthy Controlsmentioning
confidence: 89%
“…Most of the studies showed serum 25(OH)D was significantly lower in AD than HC. Of the 14 studies, only Sanmartin et al [13] and Di Filippo et al [25] showed higher 25(OH)D for AD compared with HC, but these differences were not significant. Three sub-analyses were conducted for latitude, geographical continent, and quality of study (Supplementary Figs.…”
Section: Serum Vitamin D In Atopic Dermatitis and Healthy Controlsmentioning
confidence: 89%
“…Vitamin D (VitD) can be formed in the human skin through sunlight exposure or obtained from dietary intake [ 5 , 6 , 7 ]. It is essential for the maintenance of bone health [ 6 , 8 ], regulating calcium and phosphate metabolism [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Следует также отметить, что группы детей с АтД и здоровых сверстников были сопоставимы по периодам включения в исследования (> 40% участников были включены в зимние месяцы). Вместе с тем, по некоторым данным, концентрация 25(ОН)D у детей с АтД в летний сезон выше, чем у здоровых детей, предположительно, за счет большего пребывания на солнце [26]. В связи с этим не исключено, что при формировании репрезентативной выборки за счет включения в исследование пациентов в летний период различия в концентрации 25(ОН)D не были бы обнаружены.…”
Section: ограничения исследованияunclassified
“…с АтД (18,58 ± 0,29 нг/мл) по сравнению с контрольной группой (19,20 ± 0,15 нг/мл), p = 0,02 [27]. При этом в некоторых исследованиях связь между концентрацией 25(ОН)D и АтД не была подтверждена как у детей с АтД [13,14,26], так и у взрослых с АтД [28,29]. В нашем исследовании было установлено, что более низкая концентрация 25(ОН)D ассоциирована с более тяжелым течением АтД.…”
Section: интерпретация результатов исследованияunclassified